In Vitro and In Vivo Phenotypes of Venezuelan, Eastern and Western Equine Encephalitis Viruses Derived from cDNA Clones of Human Isolates - Gardner, Christina L.; Sun, Chengqun; Dunn, Matthew D.; Gilliland, Theron C.; Trobaugh, Derek W.; Terada, Yutaka; Reed, Douglas S.; Hartman, Amy L.; Klimstra, William B. (Viruses, 2022)
The Department of Defense recently began an effort to improve and standardize virus challenge materials and efficacy determination strategies for testing therapeutics and vaccines. This includes stabilization of virus genome sequences in cDNA form where appropriate, use of human-derived virus isolates, and noninvasive strategies for determination of challenge virus replication. Eventually, it is desired that these approaches will satisfy the FDA “Animal Rule” for licensure, which substitutes animal efficacy data when human data are unlikely to be available. To this end, we created and examined the virulence phenotype of cDNA clones of prototypic human infection-derived strains of the alphaviruses, Venezuelan (VEEV INH9813), eastern (EEEV V105) and western (WEEV Fleming) equine encephalitis viruses, and created fluorescent and luminescent reporter expression vectors for evaluation of replication characteristics in vitro and in vivo. Sequences of minimally passaged isolates of each virus were used to synthesize full-length cDNA clones along with a T7 transcription promoter-based bacterial propagation vector. Viruses generated from the cDNA clones were compared with other “wild type” strains derived from cDNA clones and GenBank sequences to identify and eliminate putative tissue culture artifacts accumulated in the cell passaged biological stocks. This was followed by examination of aerosol and subcutaneous infection and disease in mouse models. A mutation that increased heparan sulfate binding was identified in the VEEV INH9813 biological isolate sequence and eliminated from the cDNA clone. Viruses derived from the new human isolate cDNA clones showed similar mouse virulence to existing clone-derived viruses after aerosol or subcutaneous inoculation.